Perilaku Merokok Pengunjung dalam Mematuhi Peraturan Kawasan Tanpa Rokok (KTR) di Lingkungan RSUD S. K. Lerik Kota Kupang - Imelda Fitryani Dam; Honey I. Ndoen; Indriati A. Tedjuhinga (Media Kesehatan Masyarakat, 2019)
Non-smoking area is a room or area that is otherwise prohibited to activities of production, sales, advertising, promotion and use of cigarettes. Regional regulation Kupang City No. 3A year 2014 about non-smoking area explain that health care facilities, including hospitals is a place or non-smoking area. S. K. Lerik Municipality General Hopital is government owned health care facilities in Kupang and non-smoking area but still a lot of casual visitors who smoke in the hospital environment. The purpose of this research was to determine the relationship between the level of knowledge, education and family environment with the behavior of visitor to comply with regulation of non-smoking area at S. K. Lerik Kupang Municipality General Hospital 2016. The method of this research was analytical surveys using the cross-sectional design. The population in this research were all those at S. K. Lerik Kupang Municipality General Hospital environment with a total sample of 384 respondents. Statistical tests were used for data analysis in this research is Chi-Square with a degree of confidence α= 0.05. The results showed that there was correlation between the level of knowledge and education with smoking behavior of the visitor at S. K. Lerik Kupang Municipality General Hospital. There was no correlation between family environment with smoking behavior of the visitors at S. K. Lerik Kupang Municipality General Hospital.